Analisis Uji Kelayakan Trainer Kit Elektronika Daya: 3 Phase Half-Wave and Full-Wave Uncontrolled Rectifier - Doni Tri Putra Yanto; Erita Astrid; Rahmat Hidayat; Syaiful Islami (Universitas Negeri Padang, 2019)
This study discusses about feasibility test analysis of power electronics trainer kit before it can be used in the learning process of power electronics practicum especially for uncontrolled 3 phase rectifiers. This testing process is carried out to ensure that the developed power electronics trainer complies with the criteria of a trainer kit that can be used in the learning process of power electronics practice. This feasibility test analysis is a laboratory level testing activity where the testing phase includes electrical testing and circuit testing. A circuit testing is carried out for 3 phase half-wave and full-wave rectifier circuits. The results showed that the developed power electronics trainer is in accordance with the criteria as a trainer kit in the learning process so that it could be applied in the learning process of power electronics practice in the laboratory. It can be concluded that power electronics trainer kit can be used as a trainer kit in the learning process of power electronics practicum